Survei Efektivitas Proses Pembelajaran Daring Akibat Pandemi Virus Corona (Covid-19) di Lapangan Tenis Meja - Wibowo Kurniawan, Ari; Iqbal Tawakal , Muhammad (Universitas Nusantara PGRI Kediri, 2022)
The main purpose of this study is to identify and conduct research on online learning methods in table tennis courses. The survey method uses a descriptive research design. A total of 180 sample respondents consisting of. Table tennis students class 2018 Department of Physical Education, Health and Recreation, State University of Malang. Questionnaires were distributed online using Google Forms. There are six sub-variables assessed regarding student learning interest, online learning advantages, online learning weaknesses, online learning facilities and infrastructure, interaction quality, and application quality. The results of the research and data analysis showed the percentage of the overall score was 56.14%, which was included in the quite effective category, so it can be concluded that online learning in the table tennis course is quite effectively applied to students majoring in Physical Education, Health and Recreation, State University of Malang class. 2018. These results still need to be reviewed again if the pandemic situation is over because it will be more effective if learning table tennis courses are carried out directly.